Far-Right Violent Extremist Women: Threats and Security Considerations - Samuels, Sarah (Women & criminal justice, 2023)
Far-right violent extremism is the most pressing form of domestic violent extremism (DVE) facing the United States. While there is a consensus that far-right violent extremism poses a genuine risk to the United States, the relevance of women within far-right violent extremism remains understated and under-researched. The misinformed perceptions about women and their propensities for violence must be acknowledged and rectified to ensure a proper analysis of the state of far-right violent extremism in the United States. The far-right social media platform Gab has been utilized to explore underlying conceptions about women in far-right extremism as well as fill the gap in the perceptions about women’s roles in extremism and violent extremism that are currently held by practitioners. A stronger commitment to the Women, Peace, and Security (WPS) agenda, a framework that reconceptualizes women within discourses about security, promises to rectify the widely held misconceptions about women’s involvement in far-right violent extremism. By reviewing the conceptual shortcomings of those tasked with protecting against far-right violent extremism, the larger goal of securing the United States and beyond can be realized.